Measuring Reliability In The Wartime Transport of Provisions: The Case of Mao Yuanyi (1594–1641). (3rd July 2019) - Hasegawa, Masato
Abstract : A military strategist and advisor, Mao Yuanyi (1594–1641) was one of the most prolific writers of the late Ming period on military matters and participated in the Ming war against the Jurchen in Liaodong in the early seventeenth century. In his seminal study on the conduct of war, the Records of Military Preparedness (Wubeizhi), he exhaustively discussed the costs and benefits of the transport methods available at the time, including carts, pack animals, and water transport. Among all the transport methods that he considered, Mao clearly favored what he called "human transport" (renyun), which exclusively relied on the labor of human bearers. By drawing on Mao's writings on the transport of provisions, this study analyzes his forceful argument in favor of employing human labor and illuminates the practices of organizing wartime logistics. It also sheds light on the manner in which the costs and benefits of transport methods were being evaluated and how the notions of efficiency and reliability came into play in calculations concerning transport in the late Ming period.